Practical utility of insulin‐like growth factor II mRNA‐binding protein 3, glucose transporter 1, and epithelial membrane antigen for distinguishing malignant mesotheliomas from benign mesothelial proliferations. (6th November 2014) - Chang, Sunhee; Oh, Mee‐Hye; Ji, Sun‐Young; Han, Joungho; Kim, Tae‐Jung; Eom, Minseob; Kwon, Kun Young; Ha, Seung Yeon; Choi, Yoo Duk; Lee, Chang Hun; Lee, Yonghee; Jung, Soon‐Hee
<x xml:space="preserve">Abstract</x> The differentiation of malignant mesotheliomas and benign mesothelial proliferations is crucial in determining patient care and prognosis. But, this distinction can be extremely difficult, particularly in small biopsies. Recently, insulin‐like growth factor II mRNA‐binding protein 3 (IMP3) and glucose transporter 1 (GLUT‐1) have been reported as specific and sensitive markers in the distinction of mesotheliomas from benign mesothelial proliferations. The purpose of this study is to evaluate the utility of IMP3, GLUT‐1, and epithelial membrane antigen (EMA) immunohistochemistry for distinguishing mesotheliomas from benign mesothelial proliferations. Immunoexpression of IMP3, GLUT‐1, and EMA was evaluated in 88 malignant mesotheliomas, 35 adenomatoid tumors, and 20 benign lung tissues with reactive mesothelial cells. The sensitivity for IMP3, GLUT‐1, and EMA was 37%, 21%, and 41%, respectively. The specificity for IMP3, GLUT‐1, and EMA was 100%. When IMP3, GLUT1, and EMA combined, the sensitivity was 66% for IMP3/EMA staining, 53% for GLUT‐1/EMA staining, and 45% for IMP3/GLUT‐1. Use of IMP3 and EMA together is more helpful to distinguish malignant mesotheliomas from benign mesothelial proliferations than the use of IMP3 or EMA alone.